The Law of the Land or the Law of the Land?: History, Law and Narrative in a Settler Society - Attwood, Bain (History compass, 2004)
This article considers the influence of a controversial historical work on the law, politics and society of a settler nation. It argues that the impact of Henry Reynolds's 1987 The Law of the Land on legal consideration of indigenous rights to land in Australia can be attributed to the fact that it is best described as juridical history. As such, it told a lego-historical story that provided the High Court of Australia with a new way of interpreting its own traditional narrative, which had long denied Aboriginal people their rights to land, thus enabling it to make a new determination of those rights as well as resolve a crisis of legitimacy for the law and the nation. This article also contends that this history-making came to be accepted by many settler Australians because it provided the nation with a newly redemptive, liberal myth narrative. It assesses the cost of a story of this kind, asking whether such simple histories can have an enduring effect, especially where their authors are reluctant to signpost the historical or literary form of their texts. Finally, it suggests that histories truer to the complexities of the past might produce better political and social outcomes.